Applying an equity lens to assess context and implementation in public health and health services research and practice using the PRISM framework - Fort, Meredith P.; Manson, Spero M.; Glasgow, Russell E. (Frontiers in Health Services, 2023)
Dissemination and implementation science seeks to enhance the uptake, successful implementation, and sustainment of evidence-based programs and policies. While a focus on health equity is implicit in many efforts to increase access to and coverage of evidence-based programs and policies, most implementation frameworks and models do not explicitly address it. Disparities may in fact be increased by emphasizing high intensity interventions or ease of delivery over meeting need within the population, addressing deep-rooted structural inequities, and adapting to local context and priorities. PRISM (Practical Robust Implementation and Sustainability Model), the contextual expansion of the RE-AIM (Reach, Effectiveness, Adoption, Implementation, Maintenance) framework has several elements that address health equity, but these have not been explicated, integrated, or illustrated in one place. We present guidance for applying PRISM with an equity lens across its four context domains (external environment; multi-level perspectives on the intervention; characteristics of implementers and intended audience; and the implementation and sustainability infrastructure – as well as the five RE-AIM outcome dimensions - and present an example with health equity considerations. We discuss issues of representation and participation, representativeness and the importance of ongoing, iterative assessment of dynamic context and structural drivers of inequity. We also elaborate on the importance of a continuous process that requires addressing community priorities and responding to capacity and infrastructure needs. We conclude with research and practice recommendations for applying PRISM with an increased emphasis on equity.